Behavior of Sandwich Tubular-hat Sections with Aluminum Foam Filler Subjected to Low Velocity Impact Load - Ly, Hung Anh; Thai Quang, Thinh (Journal of Engineering and Technological Sciences, 2017)
In this paper, a comprehensive literature review is presented regarding dynamic progressive buckling analyses of foam-filled hat section columns. The results obtained from a numerical simulation were in good agreement with the theoretical predictions. Remarks and analyses are given about the influence of aluminum foam filling in tubular-hat structures. The contribution of aluminum foam to increase both the crushing load and the mass specific energy absorption is significant. In addition, effects of geometrical parameters like wall thickness are discussed to study the role of thin walls in foam-filled hat sections.